A Brief Treatise for a Good Death: Confessions del savi peccador and its Contexts - Martínez Romero, Tomás (De Medio Aevo, 2025)
Building upon a reassessment of the concept of ars moriendi, this study proposes a broader definition of the genre, extending beyond the well-known CP and QS, traditionally regarded as “canonical.” This expanded framework allows for the inclusion of other fifteenth-century works dedicated to the preparation for a good death, which circulated either independently or as part of more extensive compositions. Among these is the  Confessions del savi peccador, a text that Fàbrega had already listed among the ars moriendi works in Catalan. The analysis of the preserved testimonies reveals that, in some cases, the work underwent a process of “literarization”: a character experiences a vision (another highly popular genre) in which he sees Jesus Christ and implores Him to bless the confessions. In an effort to heighten realism, certain versions introduce Joan Fort, a Carthusian from València renowned for his sanctity and the author of a Liber revelationum, as the main character of the vision. As a standalone work, the Confessions was also included in miscellaneous volumes alongside other pieces dealing with similar themes (temptation, sin, confession, death). This context explains the presence of a fragment from the Segon del Chrestià by Eiximenis in one such codex.
Keywords: ars moriendi; Confessions del savi peccador; Joan Fort; Liber revelationum; Eiximenis